Pre-Lightning Strikes and Aircraft Electrostatics - Fisher, J.; Hoole, Paul R.; Pirapaharan, K.; Hoole, Samuel H. (EDP Sciences, 2017)
An electric storm is a source of electrostatic charge that can induce high current and electric potential on a surface of an aircraft through direct effects. It can also be a source of radiated electromagnetic pulses on an aircraft in flight through indirect effects. Both direct and indirect effects can have adverse effects on flight safety. Thus, it is vital to gain good understanding of the pre-lightning strike and the electrical characteristics of a thunderstorm in order to quantify lightning threats to aircraft. Since lightning parameters are not easily measurable, predictive modeling can be applied to model the pre-lightning strike and aircraft electrostatics. In this paper, we applied the 3D dipole model in predicting the electrostatics build up along an aircraft extremities as it approaches an ambient electric field of a charged cloud. The results give a quantitative evaluation of the threats during pre-lightning strikes and electrostatics buildup on the aircraft. This is vital in designing and coordinating shielding measures to mitigate the threats and to harden the protection systems for aircraft.